MODEL KONSEPTUAL PERILAKU WISATAWAN MANCANEGARA PADA SUATU DESTINASI PARIWISATA: STUDI KASUS BALI SEBAGAI DESTINASI PARIWISATA INTERNASIONAL - I Nyoman Sudiarta; I Wayan Suardana (Jurnal Ilmiah Hospitality Management, 2014)
Understanding consumer behavior is an important entity in the marketing strategy, particularly in tourism destination marketing strategy. This study is a preliminary study to understand the behavior of foreign tourists at a tourist attraction in Bali, especially Sangeh tourist attraction, Kintamani and Besakih (SAKIBE). Aims to study the behavior of tourists after visiting the tourist attraction in Bali. This study uses two approaches or a combination of qualitative methods (exploratory) and quantitative (confirmatory). Exploratory studies conducted with activities focus group discussion (FGD), with tourism stakeholders especially with ASITA and HPI. The population in this study were foreign tourists who visited the three major tourist attraction of the sample size using Sugiyono, 2013 approach. While the focus group presents 8-12 resource in accordance with the rules Malhotra (2002: 351); Jennings (2001: 172). Each location will take a sample of 40, 30 and 30 on each tourist attraction that is Sangeh, Kintamani and Besakih. Data collection confirmatory studies using questionnaires given to tourists who have been in three of the major tourist attraction.